Impact of norepinephrine on immunity and oxidative metabolism in sepsis - Thoppil, Joby; Mehta, Prayag; Bartels, Brett; Sharma, Drashya; Farrar, J. David (Frontiers in Immunology, 2023)
Sepsis is a major health problem in the United States (US), constituting a leading contributor to mortality among critically ill patients. Despite advances in treatment the underlying pathophysiology of sepsis remains elusive. Reactive oxygen species (ROS) have a significant role in antimicrobial host defense and inflammation and its dysregulation leads to maladaptive responses because of excessive inflammation. There is growing evidence for crosstalk between the central nervous system and the immune system in response to infection. The hypothalamic-pituitary and adrenal axis and the sympathetic nervous system are the two major pathways that mediate this interaction. Epinephrine (Epi) and norepinephrine (NE), respectively are the effectors of these interactions. Upon stimulation, NE is released from sympathetic nerve terminals locally within lymphoid organs and activate adrenoreceptors expressed on immune cells. Similarly, epinephrine secreted from the adrenal gland which is released systemically also exerts influence on immune cells. However, understanding the specific impact of neuroimmunity is still in its infancy. In this review, we focus on the sympathetic nervous system, specifically the role the neurotransmitter norepinephrine has on immune cells. Norepinephrine has been shown to modulate immune cell responses leading to increased anti-inflammatory and blunting of pro-inflammatory effects. Furthermore, there is evidence to suggest that norepinephrine is involved in regulating oxidative metabolism in immune cells. This review attempts to summarize the known effects of norepinephrine on immune cell response and oxidative metabolism in response to infection.